Spinal muscular atrophy type 1 in the Caribbean: the first case report from the Dominican Republic - Martín-Sanz, María Belén; Lucas-Muñoz, Delvis; Colomé-Hidalgo, Manuel (Frontiers in Neuroscience, 2025)
Spinal muscular atrophy (SMA) is a progressive genetic neuromuscular condition affecting spinal motor neurons. The underlying cause of SMA is deletions or mutations in the SMN gene. It is classified into five variants based on age and clinical manifestations of the patient. In this report, we present the case discovery of a four-month-old male patient with SMA type 1, presenting with generalized hypotonia and regression of acquired neurodevelopmental milestones. Our study aims to illustrate, through a case report, the clinical analysis, therapeutic interventions, and progression until the patient’s demise. This aims to share the challenges in managing such patients and the strategies employed in their care plan. By documenting this case, our goal is to contribute to the understanding of SMA type 1 and emphasize the ongoing need for learning effective care strategies.